Respuesta :

Answer:

Given

  • f(x) = 2x² + 1
  • g(x) = 3x - 1

#1

  • f · g(5) =
  • f(g(5)) =
  • f(3*5 - 1) =
  • f(14) =
  • 2(14²) + 1 =
  • 393

#2

  • g · f(-3) =
  • g(f(-3)) =
  • g(2(-3)² + 1) =
  • g(19) =
  • 3(19) - 1 =
  • 56

#3

  • g · f(x) =
  • g(f(x)) =
  • g( 2x² + 1) =
  • 3(2x² + 1) - 1 =
  • 6x² + 3 - 1 =
  • 6x² + 2

#4

  • f · g(-x) =
  • f(g(-x)) =
  • f(3(-x) - 1) =
  • f(-3x - 1) =
  • 2(-3x - 1)² + 1 =
  • 2(9x² + 6x + 1) + 1 =
  • 18x² + 12x + 2 + 1 =
  • 18x² + 12x + 3